Specific causes of death in miners and ex-miners of the Rhondda Fach 1950-80. Issue 7 (July 1986) - Atuhaire, L K; Campbell, M J; Cochrane, A L; Jones, M; Moore, F
Abstract : The specific causes of death for miners and ex-miners of the Rhondda Fach have been examined in detail using the data base provided by the 30 year follow up. The main findings are the lower specific mortality for those with category A, compared with those with categories 0, 1, 2, and 3, for all circulatory diseases (particularly ischaemic heart disease) and the raised mortality for gastric cancer. These results are surprising because a high proportion of those with, especially, categories 2 and 3 developed category A during the 30 years but fail to show the specific death rates typical of those with category A. Possible reasons for this are discussed and an explanation put forward.